Investigation of exchange rate fluctuations on economic indicators and its management mechanism - Nezamali Vafaei (New Applied Studies in Management, Economics & Accounting, 2022)
Exchange rate fluctuations are of particular importance in macroeconomic issues due to their impact on other economic variables. Agriculture, oil, industry and services are the most important variables that are affected by currency fluctuations. Given that there have been several fluctuations in exchange rates in Iran over the past three decades, it is important to study the effect of exchange rate fluctuations on economic indicators. The purpose of this study is to investigate the effect of exchange rate fluctuations on Iran 's economic indicators. For this purpose, using annual data during the period 1991 to 2016 and using the VAR vector error correction model, the relationships between variables were examined. Therefore, in this study, the effect of real exchange rates on macroeconomic variables of the country was investigated. The results of the study indicate that the value added of the oil sector has the greatest impact on the real exchange rate. In addition, the results of the impulses of the immediate reaction and standard deviation show that if we enter a shock from the exchange rate, the oil sector variable will see the greatest effect of this shock.